Basketball players' dynamic performance across competition levels - Bullock, G. S.; Arnold, T. W.; Plisky, P. J.; Butler, R. J. (The Journal of Strength and Conditioning Research, 2018)
Dynamic balance is an integral component in screening lower extremity injury risk. Previous research has identified the need to create sport- and competition level-specific dynamic balance injury cut points. The purpose of this study was to determine if dynamic balance differences exist, using the Lower Quarter Y Balance Test (YBT-LQ), across varying competition levels (middle school, high school, college, and professional), in basketball players. Subjects were participating at the middle school (MS; n = 88), high school (HS; n = 105), college (COL; n = 46), and professional levels (PRO; n = 41). Statistical analysis was completed with a series of analysis of variance tests. Tukey post hoc tests were used to identify specific group-to-group differences if statistical significance (p = 0.05) was observed. Effect size indices (ESI) were also calculated to provide an estimate of the clinical relevance. In the anterior reach, HS basketball players performed statistically better than the MS and COL (p < 0.01, ESI = 0.58) athletes, and all these groups performed better than the PRO basketball players (p < 0.01, ESI = 1.72). For the posteromedial, posterolateral reach directions and the composite score, the HS, COL, and PRO basketball players were not significantly different from each other; however, the HS group did reach further than the MS group (p < 0.01-0.02, ESI = 0.40-0.55). The PRO basketball players exhibited a lower asymmetrical total score compared with MS, HS, and COL players (p < 0.01-0.02, ESI = 0.52-0.68). Different competition levels displayed varying dynamic balance strategies. Creating basketball competition levels normative values for dynamic balance could help define injury risk cut points.